Reaction of 1-Trimethylsilyl-1,2-epoxy-3-alkanols with Alkynes and Application to the Synthesis of 18-HEPE - Nanba, Yutaro; Morita, Masao; Kobayashi, Yuichi (Synlett, 2018)
A reaction of epoxy alcohols (anti and/or syn isomers) derived from (E)-TMS-CH=CHCH(OH)R with TMS-C≡CLi in THF/HMPA stereoselectively afforded (E)-TMS-C≡C-CH=CHCH(OH)R. The (E) stereochemistry was independent of the anti/syn stereochemistry, but the syn isomers showed higher reactivity than the anti isomers. The reaction was applied to the synthesis of (18R)- and (18S)-HEPE.
Keywords: alkynes; epoxide ring opening; silicon; stereoselective synthesis; Castro–Stephens coupling; eicosapentaenoic acid